Uncovering the Green, Blue, and Grey Water Footprint and Virtual Water of Biofuel Production in Brazil: A Nexus Perspective - Raul Munoz Castillo (Sustainability, 2017)
Brazil plays a major role in the global biofuel economy as the world’s second largest producer and consumer and the largest exporter of ethanol. Its demand is expected to significantly increase in coming years, largely driven by national and international carbon mitigation targets. However, biofuel crops require significant amounts of water and land resources that could otherwise be used for the production of food, urban water supply, or energy generation. Given Brazil’s uneven spatial distribution of water resources among regions, a potential expansion of ethanol production will need to take into account regional or local water availability, as an increased water demand for irrigation would put further pressure on already water-scarce regions and compete with other users. By applying an environmentally extended multiregional input-output (MRIO) approach, we uncover the scarce water footprint and the interregional virtual water flows associated with sugarcane-derived biofuel production driven by domestic final consumption and international exports in 27 states in Brazil. Our results show that bio-ethanol is responsible for about one third of the total sugarcane water footprint besides sugar and other processed food production. We found that richer states such as São Paulo benefit by accruing a higher share of economic value added from exporting ethanol as part of global value chains while increasing water stress in poorer states through interregional trade. We also found that, in comparison with other crops, sugarcane has a comparative advantage when rainfed while showing a comparative disadvantage as an irrigated crop; a tradeoff to be considered when planning irrigation infrastructure and bioethanol production expansion.